2015
DOI: 10.1001/jamasurg.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Association of Perioperative Hypothermia During Colectomy With Surgical Site Infection

Abstract: Patients who underwent segmental colectomy and sustained a period of intraoperative hypothermia were no more likely to develop an SSI than those who were normothermic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 12 publications
2
50
0
5
Order By: Relevance
“…A retrospective study in patients undergoing intestinal surgery showed a statistically significant relationship between a lower intraoperative temperature nadir and SSI rates, but the difference in temperature between the high versus low intraoperative temperatures was not clinically significant (35.8 ± 0.8°C vs 36.0 ± 0.9°C) [7]. Baucom et al reported on a retrospective cohort of adult patients who underwent segmental colectomies and found no correlation between intraoperative hypothermia and 30-day SSI [14]. Lastly, in patients undergoing clean operations, a retrospective series showed that duration of time and cumulative time with intraoperative hypothermia (b36°C) were not associated with SSI; in fact, higher intraoperative nadir temperatures were associated with SSI [4].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in patients undergoing intestinal surgery showed a statistically significant relationship between a lower intraoperative temperature nadir and SSI rates, but the difference in temperature between the high versus low intraoperative temperatures was not clinically significant (35.8 ± 0.8°C vs 36.0 ± 0.9°C) [7]. Baucom et al reported on a retrospective cohort of adult patients who underwent segmental colectomies and found no correlation between intraoperative hypothermia and 30-day SSI [14]. Lastly, in patients undergoing clean operations, a retrospective series showed that duration of time and cumulative time with intraoperative hypothermia (b36°C) were not associated with SSI; in fact, higher intraoperative nadir temperatures were associated with SSI [4].…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os fatores de risco associados à ISC, salienta-se, no presente estudo, a hipotermia perioperatória, a qual é indicada como fator de risco isolado para a ocorrência deste tipo de infecção em pesquisas conduzidas em diferentes centros pelo mundo (KURZ et al, 1995;LENHARDT, 1996;FLORES-MALDONADO et al, 2001;SESSLER, 2008;BAUCOM, et al, 2015). Assim, optouse, por meio de estudo de coorte, investigar o efeito da hipotermia sobre a incidência de ISC em pacientes submetidos a cirurgias abdominais.…”
Section: Infecção De Sítio Cirúrgicounclassified
“…Com relação ao potencial de contaminação da ferida cirúrgica foram incluídas cirurgias classificadas como potencialmente contaminadas ou contaminadas, sendo que as taxas esperadas de ISC são 3 a 11%, e de 10 a 17%, respectivamente (GARNER, 1986). Em estudo retrospectivo de coorte, desenvolvido em hospital terciário de referência de Nashville (EUA), com a participação de 296 pacientes submetidos à colectomia eletiva, entre 2005 e 2009, cujo objetivo foi investigar a associação de hipotermia com ISC, a taxa de infecção foi de 12,2% (em 30 dias de seguimento) (BAUCOM et al, 2015).…”
Section: Indicadores De Incidência De Infecção Do Sítio Cirúrgico (Isc)unclassified
See 2 more Smart Citations